Faktor-Faktor Yang Mempengaruhi KinerjaPegawai Pada Kantor Camat SusohKabupaten Aceh Barat Daya - Budi Safatul Anam; Zulkifli Umar; Yusnadi (BE-HISZ : Journal of Economics and Accounting, 2025)
This study aims to determine the effect of work ability, work motivation, work environment and work discipline on employee performance at the Susoh Sub-District Head Office, Southwest Aceh Regency both partially and simultaneously. The data collection method used is the method of distributing questionnaires to 24 respondents who served in the Susoh Sub-District Head Office.  While the analysis method uses multiple linear regression analysis while hypothesis testing uses the t test and F test. The results of this study indicate that work ability partially has no effect on employee performance as indicated by the significance value sig=0.546> 0.05. Work motivation partially has no effect on employee performance as indicated by a significance value of sig = 0.773 > 0.05. Work environment partially affects employee performance as indicated by a significance value of sig=0.001 <0.05. Work discipline partially affects employee performance as indicated by a significance value of sig=0.001 <0.05. Work motivation partially has no effect on employee performance as indicated by the significance value sig=0.773> 0.05. Work environment partially affects employee performance as indicated by a significance value of sig=0.001 <0.05. Work discipline partially affects employee performance as indicated by a significance value of sig=0.001 <0.05. While Work Ability, Work Motivation, Work Environment and Work Discipline simultaneously have a significant effect on Employee Performance with a calculated F value of 111.112 with a significance level (Sig.) of 0.001 which is smaller than 0.05. Thus, the better the work ability, work motivation, work environment and work discipline are applied simultaneously by the leadership, the greater the productivity of employee performance.